Edukasi Bisnis Online melalui Media Smartphone bagi Pelaku Usaha di Desa Pete Kabupaten Tangerang - Winanti, Winanti; Sudiyono, Rachma Nadhila; Oktarina, Thina; Rizfie, Muhammad Dala; Hartati, Ria; Maesaroh, Siti; Jainuri, Jainuri; Sukriyah, Sukriyah; Silitonga, Nelson; Tiara, Beby; Riyanto, Riyanto; Fernando, Erick; Yusuf, Yusuf; Yunitasari, Yunitasari; Lestari, Sri (IAHN Gde Pudja Mataram, 2025)
Online business education activities with smartphones are carried out because there are still many business actors who have not utilized their smartphones to carry out various business processes ranging from product offerings, sales to payment transactions. The purpose of the activity is to educate and provide understanding to the public about online business with smartphone media. The methods used are lectures, discussions and direct practice in front of MSME actors. The expected results of this activity are increased promotion and sales as well as an increase in the standard of living of business actors who are members of the Pete Village community business incubation program, Tigaraksa Tangerang